2022
DOI: 10.1042/bcj20210767
|View full text |Cite
|
Sign up to set email alerts
|

Co-evolution of drug resistance and broadened substrate recognition in HIV protease variants isolated from an Escherichia coli genetic selection system

Abstract: A genetic selection system for activity of HIV protease is described that is based on a synthetic substrate constructed as a modified AraC regulatory protein that when cleaved stimulate L-arabinose metabolism in an Escherichia coli araC strain. Growth stimulation on selective plates was shown to depend on active HIV protease and the scissile bond in the substrate. In addition, the growth of cells correlated well with the established cleavage efficiency of the sites in the viral polyprotein, Gag, when these sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
(28 reference statements)
1
1
0
Order By: Relevance
“…Margerison et al 23 identified K55R associated with M46I/L, which is in line with our evolutionary model that presents M46I as an ancestor and M46L as a descendant of K55R. I66V and E34Q have previously been identified as resistance mutations during PI treatment 24–27 . Mutation V118I is known to be associated with resistance to the NRTI class 28 .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Margerison et al 23 identified K55R associated with M46I/L, which is in line with our evolutionary model that presents M46I as an ancestor and M46L as a descendant of K55R. I66V and E34Q have previously been identified as resistance mutations during PI treatment 24–27 . Mutation V118I is known to be associated with resistance to the NRTI class 28 .…”
Section: Resultssupporting
confidence: 87%
“…I66V and E34Q have previously been identified as resistance mutations during PI treatment. [24][25][26][27] Mutation V118I is known to be associated with resistance to the NRTI class. 28 It also plays a part in dual resistance to AZT and 3TC together with mutation E44D.…”
Section: Frequency Matrixmentioning
confidence: 99%